Technical report for interventions in Kijichi Primary school: White paint, new roofs and ceiling boards - Regime Projects Tanzania; Open Development & Education (Open Development & Education, 2024)
An output of the Open Development & Education, https://opendeved.net/
Keywords: Internal; _r:AddedByMyEducationEvidence